World Journal of Pediatrics - Zhao, Zheng-Yan.; SpringerLink (Online service) (Singapore : Springer Singapore : Imprint: Childrens Hospital, Zhejiang University School of Medicine, co-published with Springer.)
World Journal of Pediatrics, a quarterly journal, publishes peer-reviewed original papers, reviews, and special reports focusing on clinical practice and research in pediatrics. Contributions on new developments in all areas of pediatrics are welcome from pediatricians worldwide. The journal aims at providing the most current information on pediatrics, pediatric surgery, preventive health care in pediatrics, pharmacology, stomatology and biomedicine. The journal also deals with basic sciences and experimental work. It provides a broad academic platform for the international exchange of medical results. All submitted papers are peer-reviewed by at least two referees who are experts in the field of the submitted paper. World Journal of Pediatrics wants to be as efficient as possible in manuscript processing. All authors shall receive the final decision on their submitted papers within two months. Outstanding papers or special reports might be accepted within one month after submission; the journal will try then to publish these contributions in the next available issue. We are expecting your contributions.
Keywords: Maternal and child health services; Radiology; Critical care medicine; Pediatrics; Surgery; Pediatric surgery; Pediatrics; Pediatric Surgery; Maternal and Child Health; Intensive / Critical Care Medicine; Surgery; Imaging / Radiology